2021
DOI: 10.1007/978-3-030-85521-5_2
|View full text |Cite
|
Sign up to set email alerts
|

To Work from Home (WFH) or Not to Work from Home? Lessons Learned by Software Engineers During the COVID-19 Pandemic

Abstract: This research investigates software engineering during the COVID-19 pandemic with a focus on the lessons learned and predictions for future software engineering work. Four themes are explored: Remote work, Team management, Work/Life balance, and Technology/Software Engineering Methods. Our research has demonstrated that software companies will derive tangible benefits from supporting their employees during this uncertain time through ergonomic home offices, listening to their concerns, as well as encouraging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Based on the finding that points out the negative effect of job strain on the dependent variables, the influence of factors such as hobbies, or virtual socialization events outside work that may replenish personal resources for software workers could be investigated further to mitigate the negative effect of job strain during pandemic home-based work. Managers or supervisors could be in constant communication with software practitioners and support their periodic breaks as suggested by Nolan et al (2021) as well.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the finding that points out the negative effect of job strain on the dependent variables, the influence of factors such as hobbies, or virtual socialization events outside work that may replenish personal resources for software workers could be investigated further to mitigate the negative effect of job strain during pandemic home-based work. Managers or supervisors could be in constant communication with software practitioners and support their periodic breaks as suggested by Nolan et al (2021) as well.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing communication over such conditions is more challenging which eventually impacts the productivity of software development teams (Yag€ ue et al, 2016). Recent researchers have also explored that as most of the software teams are working in virtual space during the COVID-19 Pandemic, these are one of the biggest challenges for software teams and it is having negative effects on the well-being, behaviors as well as productivity of the software developers (Russo et al, 2021;S ¸ent€ urk et al, 2021;Nolan et al, 2021;Marek and Wi nska, 2021). In such a stressful environment it is observed that the ability of the Agile software development teams to adapt to the Agile mindset gets impacted.…”
Section: Behaviours Of Agile Software Development Team During the Cov...mentioning
confidence: 99%
“…Also, positive trends are found in longitudinal surveys, i.e., developers' productivity in the later months of the pandemic show better results than those in the earlier months. Nolan et al conducted a qualitative study on software engineering during the COVID-19 pandemic [13]. The authors showed that software companies will derive tangible benefits from supporting their employees during this uncertain time through ergonomic home offices, listening to their concerns, as well as encouraging breaks and hard stops to boost long term well-being and productivity.…”
Section: Work From Home and Software Engineeringmentioning
confidence: 99%
“…On one hand, research about the relationship between working conditions and individual characteristics, i.e. productivity, well-being and work-life balance have been quite well explored in software project context [13,14,15,16,17,18]. These studies conceptualize constructs, such as well-beingness, fear, stress, distractions, communication and happiness and relate them to individual performance on different software engineering activities.…”
Section: Introductionmentioning
confidence: 99%